Gaya Kepemimpinan Kepala Madrasah Dalam Menangani Koflik Interpersonal Di Madrasah Ibtidaiyah Aswaja Sumberjo Umbulsari Jember - Nuruddin, Virly; Nuruddin (Cendekia : Jurnal Pendidikan dan Keagamaan, 2024)
The purposes of this research are: 1) To describe how the leadership style of the madrasa head in dealing with conflicts between the head of the madrasa and teachers at Madrasah Ibtidaiyah Aswaja Umbulsari Jember. 2) To describe how the leadership style of the madrasa principal deals with conflicts between teachers and teachers at Madrasah Ibtidaiyah Aswaja Umbulsari Jember. 3) To describe how the leadership style of the madrasa principal deals with conflicts between students and students at Madrasah Ibtidaiyah Aswaja Umbulsari Jember. This research uses a qualitative research approach with a descriptive qualitative type. The data analysis technique used in this study uses data analysis techniques from Miles, Huberman, and Saldana, namely data condensation, data presentation, and data verification/conclusion. The results of this study are: 1) The leadership style of the madrasa head in dealing with conflict between the madrasa head and teachers is a democratic leadership style with a collaborative conflict resolution strategy. 2) The leadership style of the madrasa head in dealing with conflicts between teachers and teachers is a democratic leadership style with compromise/negotiation conflict resolution strategies. 3) The leadership style of the madrasa principal in dealing with conflicts between students and students is a democratic leadership style with a collaborative conflict resolution strategy.